Teen Identity and K-Pop Fanaticism: Gender Perspectives and Implications for Guidance Services with A Systematic Literature Review - Adawiyah, Ratu Amanda Rabiatul; Damayanti, Rika; Masya, Hardiansyah (Yayasan Ilomata, 2025)
This study focuses on K-Pop fanaticism and its impact on the development of adolescent self-identity, with a particular focus on gender differences. The aim of this study is to examine how adolescents' involvement in K-Pop fandom influences their identity formation and its implications for self-development through personal counseling services. The method used is a Systematic Literature Review of articles in the Scopus database (2015–2024). The results of the study indicate that adolescents' involvement in K-Pop fandom can shape social and personal identities, but also pose risks such as excessive fanaticism and gender role distortion. Gender differences influence how adolescents internalize fandom culture, which directly impacts the dynamics of their self-development. These findings highlight the importance of personal guidance services that are responsive to popular cultural phenomena and sensitive to gender issues in order to support healthy and balanced adolescent identity development.